The Effects of a Liquid Dentifrice Containing an Antibacterial Agent and Anti-inflammatory Agents on The Prevention of Periodontal Disease - FUJITA, Kouji; OHISHI, Mika; ANAI, Kyoichi; WATANABE, Yukio; NAKAGIMA, Keiji; IKEDA, Katsumi; OHTSUKA, Hideharu; SHIMOJIMA, Takahiro; SUDOU, Youtarou; KURIHARA, Noriyoshi; TATSUMI, Junichi; OBARA, Toshihiko; et al. (Nihon Shishubyo Gakkai Kaishi (Journal of the Japanese Society of Periodontology), 1994)
The purpose of this clinical study was to evaluate the effects of a test liquid dentifrice containing 0.1% triclosan, 0.05% tranexamic acid and 0.05% dipotassium glycyrrhizinate on the control of dental plaque, and the prevention and/or improvement of periodontal disease in comparison with a placebo dentifrice. Subjects were 60 adults who had no serious oral and systemic disease. They were divided into two groups of equal size and performed toothbrushing twice a day for fuor weeks. The results were summarized as follows: 1) The test liquid dentifrice was significantry superior to the placebo dentifrice in improving the gingival index (P<0.01) and the plaque index P<0.01). (2) No particular side effects were observed during this clinical study.